Responses in Growth and Anatomical Traits of Two Subtropical Tree Species to Nitrogen Addition, Drought, and Their Interactions - Li, Yiyong; Wang, Zhaocheng; Liu, Huihui; Zhang, Cheng; Fu, Songling; Fang, Xiong (Frontiers in Plant Science, 2021)
Nitrogen (N) deposition and drought are two major stressors that influence tree growth and propagation. However, few studies have investigated their interactions. In this study, saplings of two co-occurring species, Ormosia pinnata (leguminous) and Schima superba (non-leguminous), were cultivated under two N addition rates (0 and 80 kg N ha-1 y-1) with well-watered (WW, 80% of field capacity), moderate drought (MD, 60% of field capacity), and severe drought conditions (SD, 40% of field capacity). We examined their growth, as well as multiple anatomical and non-structural carbohydrate (NSC) responses after two years. Results revealed that N addition significantly promoted the growth of MD-stressed S. superba, whereas no significant effect was detected in O. pinnata. Decreased leaf water potential (both Ψmd and Ψpd) was observed with N addition for both species under MD, but not under SD. The application of N positively impacted drought adaptive responses in stem xylem of S. superba, showing decreased stem xylem vessel diameter (DH), theoretical hydraulic conductivity (Kth) and increased vessel frequency (VF) upon drought under N addition, while such impacts were not observed in O. pinnata. Regarding leaf anatomy, N addition caused drought-stressed S. superba to generate leaves with a lower density of vein (VD) and stomata (SD). This potentially contributed to an enhanced acclimation to drought, whereas it decreased the palisade mesophyll thickness (PMT) of SD-stressed O. pinnata. Moreover, N addition increased the xylem soluble sugar and starch of MD-stressed O. pinnata, and decreased the xylem soluble sugar under SD for both species. Our results suggest that N addition does not consistently modify tree growth and anatomical traits under variable water availability. S. superba appeared to have a greater capacity to be more adaptable under the future interactive effects of N addition and drought due to major modifications in its anatomical traits.